How to interpret the Qurʾān: a moral issue? (Doctor Virtualis, 2022)
There are many different approaches to interpreting scripture, and the Qurʾān in particular, and these tend to work with different theories of meaning. After all, the issue is what a particular text actually means, and we need a theory about how to resolve such questions, especially when there are apparent difficulties in understanding the text. Arguments tend to range over which theory of meaning makes most sense of the text, or works most adequately as a theory of meaning. One approach which has not been taken on the whole is to see the issue as partially at least moral and epistemological. Should we have confidence that we can understand entirely what is before us, and how would we know that we have the answer to the semantic issues that any such text brings along with it? It might be argued that an ethics of moderation, balance, and restraint are important hermeneutic techniques that up to now have not been sufficiently employed when discussing how to understand and interpret the Qurʾān.
Keywords: Qurʾān; Hermeneutic; Tradition; taqwā (Piety)